2017
DOI: 10.1007/s00221-017-5140-z
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory enhancement elicited by unconscious visual stimuli

Abstract: The merging of information from different senses (i.e., multisensory integration) can facilitate information processing. Processing enhancements have been observed with signals that are irrelevant to the task at hand, and with cues that are non-predictive. Such findings are consistent with the notion that multiple sensory signals are sometimes integrated automatically. Multisensory enhancement has even been reported with stimuli that have been presented subliminally, though only with meaningful multisensory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 49 publications
8
21
2
Order By: Relevance
“…When performing the task, rats showed shorter reaction times in multisensory conditions. This result is consistent with what was observed in many previous studies conducted in both humans and animals [40][41][42][43]. Of especial relevance to our finding here, it has been shown that a task-irrelevant auditory stimulus could shorten the reaction time of responding to visual cues [44] and multisensory processing of both semantic congruent and incongruent stimuli could speed up reaction time [42].…”
Section: Discussionsupporting
confidence: 94%
“…When performing the task, rats showed shorter reaction times in multisensory conditions. This result is consistent with what was observed in many previous studies conducted in both humans and animals [40][41][42][43]. Of especial relevance to our finding here, it has been shown that a task-irrelevant auditory stimulus could shorten the reaction time of responding to visual cues [44] and multisensory processing of both semantic congruent and incongruent stimuli could speed up reaction time [42].…”
Section: Discussionsupporting
confidence: 94%
“…However, unusually high RT variability was noted in this first attempt compared to the previous studies by Barutchu et al in which the experimenter was seated in the room with the participant, the most obvious explanation being the absence of the experimenter from the testing room (e.g., Barutchu et al, 2009Barutchu et al, , 2018. Within the multisensory literature, in studies that test children and clinical patients, for reasons of practicality, participants are often closely monitored with the experimenter or caregiver typically seated in the room (e.g., Barutchu et al, 2009Barutchu et al, , 2018Bremner et al, 2012). However, in adult studies, participants are typically left alone during the testing phase of any experiment.…”
Section: Methodscontrasting
confidence: 48%
“…Initially, the two experiments reported here were designed to replicate prior findings by Otto and Mamassian, and the experiment was conducted with the participants left alone in a quiet isolated room (e.g., Otto and Mamassian, 2012). However, unusually high RT variability was noted in this first attempt compared to the previous studies by Barutchu et al in which the experimenter was seated in the room with the participant, the most obvious explanation being the absence of the experimenter from the testing room (e.g., Barutchu et al, 2009Barutchu et al, , 2018. Within the multisensory literature, in studies that test children and clinical patients, for reasons of practicality, participants are often closely monitored with the experimenter or caregiver typically seated in the room (e.g., Barutchu et al, 2009Barutchu et al, , 2018Bremner et al, 2012).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Priming refers to an increased sensitivity to certain stimuli, resulting from prior exposure to related visual or audio messages [ 1 ]. When an individual is exposed to the word “cancer”, for example, and then offered the choice to smoke a cigarette, we expect that there is a greater probability that they will choose not to smoke as a result of the earlier exposure.…”
Section: Introductionmentioning
confidence: 99%